Assessing the early performance of bifacial floating PV system: A comparative study - Islam, Md. Imamul; Mohd Shawal, Jadin; Ruhaizad, Ishak (IEEE, 2024)
The increasing need for energy and the limited amount of land have made floating photovoltaic systems gain attention as a possible alternative. Although FPV systems have existed for more than ten years, their extensive use has gained significant traction in recent years. This research investigated the initial performance of a 157.20 kWp bifacial floating photovoltaic system located on Lake B at Universiti Malaysia Pahang Al-Sultan Abdullah, Pekan, Malaysia, utilising 2,574 m2 of lake waterbodies. The system was launched during the last week of November 2023. The data collection, which took place from December 2023 to April 2024, shows notable fluctuations in energy production and performance ratio, emphasising the impact of seasonal factors. To get a deeper understanding of the system, a comparative study was performed on real performance data and the results from a PVsyst simulation model. The simulation model, using parameters similar to those of the operational system, projected greater energy yields and performance ratios than the actual observations in the field. The difference between simulation and real data highlights the difficulties in converting theoretical concepts into practical situations. Various factors might impact performance, including lower irradiation, potential-induced deterioration, temperature losses, and inverter inefficiencies. In addition, the simulation and comparison analysis of monofacial and bifacial FPV systems did not reveal any significant benefit of bifacial systems over monofacial systems. The findings of the study highlight the need for rigorous monitoring and assessment of FPV systems to close the disparity between theoretical expectations and actual results.